Are Non-reef Habitats as Important to Benthic Diversity and Composition as Coral Reef and Rubble Habitats in Submarine Canyons? Analysis of Controls on Benthic Megafauna Distribution in the Porcupine Bank Canyon, NE Atlantic - Appah, J. K. M.; Lim, A.; Harris, K.; O’Riordan, R.; O’Reilly, L.; Wheeler, A. J. (Frontiers in Marine Science, 2020)
Submarine canyons support high biomass communities as they act as conduits where sediments, nutrients and organic matter from continental shelves, or carried along by slope currents, are transported into the abyssal zone. The upper Porcupine Bank Canyon (uPBC), located on the Irish continental margin isolated from terrigenous inputs, reveals a complex terrain and substrate variation that affect the distribution of benthic fauna. Here, ROV-based benthic video, Conductivity-Temperature-Depth (CTD), current velocity profiles, suspended particulate organic matter (POM) and bathymetric data were assessed to determine the controls on the distribution of benthic megafauna throughout the canyon. Multivariate analysis of the benthic community reveals significant (P < 0.05, 0.091 < R < 0.166) differences in community structure between habitats and site locations throughout the canyon. Furthermore, these results show that non-coral reef habitats exhibit more variation in the composition of benthic taxa than coral reef habitats, with the following taxa contributing most to the structural differentiation: Leiopathes glaberrima (12.46%), Hexadella dendritifera (10.37%), Cidaris cidaris (9.31%), Aphrocallistes beatrix (9.33%), Areaosoma fenestratum (9.11%), Stichopathes cf. abyssicola (7.39%), Anthomastus glandiflorus (4.66%) and Benthogonea rosea (3.84%). In addition, a greater diversity, taxa evenness and a high abundance of mobile fauna were observed in non-coral reef habitat and the canyon flank. Seabed terrain features (depth, slope) are the most important environmental drivers that affect benthic taxa distribution while site locations and habitat type slightly influence taxa distribution in the uPBC. The highest mean current speed was observed on the canyon flank where the highest Shannon’s diversity was recorded while mean current speed ranged from 18.2 - 31.3 cm s-1. As the PBC is cut off from direct terrigenous input, this research allows to understand cold-water coral habitat responses to natural Northeast Atlantic environmental conditions. The findings of the current study will inform key stakeholders on how to responsibly interact with the upper canyon benthic habitats and can help inform policy makers on the effective conservation and management of the cold water coral (CWC) habitat in the uPBC and other canyons.